2018
DOI: 10.4178/epih.e2018028
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air quality and subjective stress level using Community Health Survey data in Korea

Abstract: OBJECTIVESAir pollution causes various disease in exposed populations, and can lead to premorbid health effects manifested as both physical and psychological functional impairment. The present study investigated the subjective stress level in daily life in relation to the level of air pollution.METHODSData from the Community Health Survey (2013), comprising 99,162 men, and 121,273 women residing in 253 healthcare administrative districts, were combined with air pollutant concentration modelling data from the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Choi et al showed that the spatial distributions of PM 10 , PM 2.5 , and NO 2 with data assimilation over China and the Korean peninsula accurately depicted the observed air quality at the monitoring stations [36]. Further details of data assimilation are available in Choi et al's study, and these data have also been validated in a previous study [36,37].…”
Section: Exposure Modelingmentioning
confidence: 88%
“…Choi et al showed that the spatial distributions of PM 10 , PM 2.5 , and NO 2 with data assimilation over China and the Korean peninsula accurately depicted the observed air quality at the monitoring stations [36]. Further details of data assimilation are available in Choi et al's study, and these data have also been validated in a previous study [36,37].…”
Section: Exposure Modelingmentioning
confidence: 88%
“…First, we only estimated data on the concentrations of specific air pollutants across the country using the KAQFS rather than including real air pollutant measurement concentrations because of the limited number of air-quality monitoring stations. Moreover, the real measurement data cannot fully reflect the air pollution exposure at participants’ residences [ 15 ]. The data assimilation method, similar to the KAQFS, could support simultaneous data fusion for multiple pollutants and accurately represent current air quality [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KAQFS included the Sparse Matrix Operator Kernel Emissions version 2.7 and Community Multiscale Air Quality version 4.7.1, which used emission inventories, including the Multi-Resolution Emission Inventory for China, Regional Emission Inventory in Asia, and Clean Air Policy Support System [ 14 ]. Detailed descriptions of the model have been published previously [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations